THE ANALYSIS OF CONFLICTS REFLECTED BY MAI CHARACTERS IN “RISE OF THE GUARDIANS” MOVIE - Putri Rachmawati (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2018)
This study focuses on the analysis of the main characters; Jack Frost, Santa Claus, the Tooth Fairy, the Easter Bunny, Pitch Black, and the Sandman’s internal and external conflicts in “Rise of the Guardians” Movie. The purpose of this study is to find out type of the internal and external conflicts based on the William Kenney’s theory. The study was conducted by using descriptive qualitative approach. The findings of this study; internal conflict: Jack Frost vs. Himself and the external conflict include Santa Claus vs. Yeti, Jack Frost vs. Easter Bunny, Pitch Black vs. Group of Guardians, Jack Frost vs. Group of Guardians, Jack Frost vs. Pitch Black. The problem solving of those conflict is competitive, because the Group of the Guardians pursues their own concerns at the Pitch Black’s expense. Key Words: Conflict, main character, rise of the guardians, movie